2014
DOI: 10.1002/adv.21418
|View full text |Cite
|
Sign up to set email alerts
|

Photopolymerization Kinetics of Block Polyether Based Terminal Urethane Methacrylate with/without Cross‐Linker

Abstract: The present work deals with the photopolymerization of difunctional macromonomer with a polyether chain and urethane methacrylate terminations. Macromonomeric formulations were prepared by mixing macromonomer with two different concentrations of photoinitiator. Formulations were also prepared by the addition of 10 wt% of soft-segmented difunctional cross-linker to the abovementioned macromonomic formulations. All formulations were then subjected to photopolymerization studies and the effects of light intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Because the gelation of the samples at an early stage of the reaction, in which phase separation in monomer-polymer mixtures occurred, hindering the termination reaction [38]. On the other hand, T g of the formulations in the study were found to be around 50-90 • C. Hence, the system vitrified on cure as the analysis isothermal temperatures were lower than the ultimate T g observed on cure, what also reduced the extent of double bond conversion [39,40].…”
Section: Samplementioning
confidence: 77%
“…Because the gelation of the samples at an early stage of the reaction, in which phase separation in monomer-polymer mixtures occurred, hindering the termination reaction [38]. On the other hand, T g of the formulations in the study were found to be around 50-90 • C. Hence, the system vitrified on cure as the analysis isothermal temperatures were lower than the ultimate T g observed on cure, what also reduced the extent of double bond conversion [39,40].…”
Section: Samplementioning
confidence: 77%
“…Viscosity is an important property of oligomers that controls the diffusion process in photopolymerization reactions . Figure shows the viscosity of NEA resins at 60°C.…”
Section: Resultsmentioning
confidence: 99%
“…Viscosity is an important property of oligomers that controls the diffusion process in photopolymerization reactions. 26 Figure 3 shows the viscosity of BFA blends with different HEMA-DDSA contents at room temperature. The viscosity of BFA oligomer was found to be higher than 1 × 10 5 mPa s. According to the experimental data, the addition of HEMA-DDSA and TMPTA could reduce the viscosity of the UV-curing system effectively.…”
Section: Viscositymentioning
confidence: 99%